PEMANFAATAN TEPUNG KULIT PISANG DAN AMONIASI JERAMI MENGGUNAKAN TEPUNG ROTI AFKIR DALAM RANSUM KAMBING KEJOBONG JANTAN - Suparwi Suparwi; Sri Utami Sri Utami (AGRICOLA, 2014)
In Kejobong, Purbalingga, goat population was approximately 15,000..In dry season it is difficult to provide food for goats,  so they have to dug out of pens to browse the agricultural waste.Banana peel and rice straw are widely available in the study sites. Fresh banana peelshould be dried and converted intoflour as goat’s diet.Rice straw was processed through ammonization added with waste bread meal to enhance its quality. Three different concentrations of R0 without banana peel flour in concentrate,  R110% and R2 of 20%. as a substitute for fresh forage is hay ammoniation is  a treatment at 18 kejobong male goats which are divided into six groups of weights. Research design used was randomized block design. Ration  based on voluntary feed intake measured during preliminari for 14 days. Subsequent consumption of the feed ration as a standard ration and the addition is adjusted to increase the weight that weighed every two weeks.Results showed that flour banana peel to the extent of 20% was not different (P <005) against the daily body weight gain and feed consumption, but different (P >0.01) of meat-bone ratio and weight group  as such, flour banana peel  to some degree 20% can be used as feed concentrate for kejobong male goat.